2016
DOI: 10.1177/0031512516637019
|View full text |Cite
|
Sign up to set email alerts
|

Dysfluent Handwriting in Schizophrenic Outpatients

Abstract: Taking into account findings in the literature, the author aimed to test whether specific graphical characteristics of handwriting can distinguish patients diagnosed with schizophrenic disorders from healthy controls. Handwriting samples (one sample from each person) from 60 outpatients (29 women, 31 men; age M = 28.5, SD = 5.4) with paranoid schizophrenia were analyzed by three documents examiners and were compared to samples from 60 controls (30 men, 30 women, age M = 28.0, SD = 3.0) without psychiatric diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For this reason, other methods have been proposed such as the recording of handwriting movements [29–32]. Several studies have found that some features of handwriting may be an objective measure of MA and a useful complement to the clinical assessment of patients [3338]. In this line of research, studies differ in the specific measures employed.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, other methods have been proposed such as the recording of handwriting movements [29–32]. Several studies have found that some features of handwriting may be an objective measure of MA and a useful complement to the clinical assessment of patients [3338]. In this line of research, studies differ in the specific measures employed.…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, a factor differentiating the handwriting of prisoners and non-prisoners is a synthetic feature, e.g., degree of writing fluency (for example, Goc [21] stresses the importance of synthetic features) or other uncontrolled factors (e.g., micro-damage to the central nervous system) which have a key impact on the differences detected in the handwriting parameters of prisoners and non-prisoners. These differences can be also associated with a prison situation and stress or any negative emotional states influencing the handwriting parameters [24]. The key comparisons between two incarcerated samples showed that no specific parameters measured by Global-Graf { XE "GlobalGraf" } computer programs were associated with PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, research has employed diverse measures of handwriting in the study of motor symptoms in psychotic disorders (Caligiuri et al, 2015;Gawda, 2016). Motor symptoms were first studied in psychosis as side effects of the antipsychotic treatment (Chengappa et al, 1994;Simpson and Lindenmayer, 1997).…”
Section: Introductionmentioning
confidence: 99%